Isolation of Bacillus thuringiensis from Type B Tidal Lands - Mila, Mila; Rizali, Akhmad; Saputra, Riza Adrianoor; Sari, Yulia Padma (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2024)
Bacillus thuringiensis is a disease-causing bacterium in insects that is used to control insect pests that attack crops, both crops and horticultural crops. This bacterium can be isolated from plant residues that have become compost, infected insects, and soil. Isolation was carried out to take bacteria from their natural environment and grow them in artificial media. In swamps, there are important microorganisms involved in the decomposition of organic matter. The microbes that play a role consist of fungi and bacteria, for instance, those are found in rice plantations in Barito Kuala swamps, which include the Actinomycetes, Bacillus, Cromobacterium, and Pseudomonas bacteria groups. B. thuringiensis is widely distributed in nature but is rare due to the many different Bacillus isolates. Therefore, it was necessary to conducted research to determine the presence of B. thuringiensis in plant root areas in more specific soils to increase the possibility of finding B. thuringiensis. This study aims to determine the number of B. thuringiensis isolates obtained in type B tidal land ecosystems. This research was conduct from December 2021 to June 2022 at the Integrated Laboratory and Production Laboratory, Department of Agroecotechnology, Faculty of Agriculture, University of Lambung Mangkurat. This research used a descriptive method. Soil collection was carried out by purposive sampling (sampling technique with certain considerations) in the planting area in tidal land type B. Soil samples were taken from 3 places as a comparison, namely in the rice planting area, orange planting area, and banana planting area B. The parameters observed in this study were the number of colonies, the macroscopic and microscopic shape characteristics of the bacteria, the gram of bacteria, and the test of the killing power of bacteria against P. xylostella insects. Based on the parameters that have been observed, the highest number of colonies was found in citrus plantation samples, with 98 colonies.